Impact of proximal cavities and primary molar absence on space in the dental arches - Gomide,Rafael T.; Frencken,Jo E.; Leal,Soraya C.; Kuijpers-Jagtman,Anne Marie; Faber,Jorge (PeerJ, 2020)
Background A recently proposed treatment protocol for dental caries in primary teeth, called Ultra Conservative Treatment (UCT), keeps medium to large cavities open so that children can keep them clean with tooth brushing and fluoride toothpaste. However, carious lesions have been related to malocclusion and decrease of space for the eruption of the permanent successor. Methods This cross-sectional study evaluated dental casts of 235 schoolchildren, aged 6–7 years old of six public schools in deprived suburban areas, and with at least two cavitated dentin carious lesions. The casts were grouped according to the location of cavitated dentin lesions into non-proximal cavity (NPC), proximal cavity with buccal or lingual surface contact point to adjacent tooth (PCCP) and proximal cavity without contact to adjacent tooth (PCWC), as well as the absence of primary molars due carious lesions (PMA). The relationship between location of cavitated dentin lesions or absence of primary molars with C+D+E and D+E space was analyzed. Results Children with absence of primary molars exhibited the smallest C+D+E and D+E space in the maxilla (P < 0.001) and mandible (P < 0.001), followed by proximal cavity without buccal or lingual surface contact. No significant difference was observed between NPC and PCCP groups in upper and lower arches. Discussion PCWC are associated with minor (less than the leeway space) C+D+E and D+E space loss in both arches, and additional space loss is noted when primary molars are prematurely lost. These results may have implications for orthodontic and restorative dental care decisions in children.
Keywords: Primary dentition; Atraumatic restorative treatment; Tooth migration; Premature tooth loss; Malocclusion